Altered dynamic functional architecture in type 2 diabetes mellitus - Li, Yifan; Li, Mingrui; Zhao, Kui; Wang, Yan; Tan, Xin; Qin, Chunhong; Rao, Yawen; Sun, Zhizhong; Ge, Limin; Cao, Zidong; Liang, Yi; Qiu, Shijun (Frontiers in Endocrinology, 2023)
Type 2 diabetes mellitus (T2DM) can accelerate cognitive decline and even dementia so that the underlying mechanism deserves further exploration. In the resting state, brain function is still changing dynamically. At present, it is still unknown whether the dynamic functional connectivity (dFC) between various brain regions is in a stable state. However, few studies have explored the stability of dFC, that is, the stability of brain architecture. In this study, we used a fixed dynamic time scale to explore the stability of dynamic functional architecture in T2DM, then the dynamic effective connectivity (dEC) was used to further explain the how information flows through dynamically fluctuating brain architecture in T2DM. There were two brain regions with decreased stability were found which contain right supra-marginal gyrus (SMG) and right median cingulate gyrus (MCG) in T2DM subjects. The dEC variation has increased between left inferior frontal gyrus (IFG) and right SMG. The direction of causal flow is from right SMG to left IFG. The combination of stability and dEC can not only show the stability of dynamic functional architecture in brain, but also reflect the fluidity of brain information, which is an innovative and interesting attempt in the field of neuroimaging. The stability changes of dynamic architecture in T2DM patients may present an innovative perspective and explanation for their cognitive decline.